1982
DOI: 10.1128/jvi.42.1.283-291.1982
|View full text |Cite
|
Sign up to set email alerts
|

Ψ, a Temperate Phage of Agrobacterium tumefaciens , Is Mutagenic

Abstract: A new temperate bacteriophage (phage '1) of Agrobacterium tumefaciens strain B91 is described. Many octopine-utilizing strains of A. tumefaciens harbor prophage 4 or a phage that is similar if not identical to it. This phage has a very narrow host range, and we found that its growth is strongly reduced in strains which carry an octopine pTi plasmid. When sensitive bacteria are infected with 4, 1 to 3% of the survivors carry mutations on the chromosome, as well as on the pTi plasmid. This phenomenon appears to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A . tumefaciens phage research began in the 1960s, though many of the isolated phages were found to be lysogenic (De Ley et al, 1972; Expert & Tourneur, 1982; Korant & Pootjes, 1970). One of the first highly virulent phages isolated was PB21 in 1967 (Stonier et al, 1967).…”
Section: Phages For Treatment Of Bacterial Tree Diseasesmentioning
confidence: 99%
“…A . tumefaciens phage research began in the 1960s, though many of the isolated phages were found to be lysogenic (De Ley et al, 1972; Expert & Tourneur, 1982; Korant & Pootjes, 1970). One of the first highly virulent phages isolated was PB21 in 1967 (Stonier et al, 1967).…”
Section: Phages For Treatment Of Bacterial Tree Diseasesmentioning
confidence: 99%
“…There are few studies concerning agrobacterial bacteriophages and perspectives of their use in biological control of crown gall [9,20,28,35,100,108]. Eayre C. (2003) informed about the possibility of walnut crown gall control using bacteriophages [34].…”
mentioning
confidence: 99%